Determinants of Low Utilization of Integrated Health Posts (Posyandu) in Tumbang Samba: The Role of Age, Educational Level, Knowledge, and Motivation - Sri Susanti; Titik Istiningsih (SIGn Journal of Public Health, 2025)
The health monitoring coverage for children under five in Katingan Regency remains low at 45.6%, falling significantly below the national strategic target. This situation necessitates an epidemiological evaluation to identify the underlying determinants of this phenomenon. This study aimed to quantitatively analyze the factors associated with the utilization of Integrated Posyandu by mothers of under-five children within the catchment area of Tumbang Samba Public Health Center. An analytic observational study with a cross-sectional design was conducted among 108 mothers of children under five, selected through purposive and incidental sampling. Data were collected using structured questionnaires and Maternal and Child Health (MCH) handbooks, and bivariate analysis was performed using the nonparametric Chi-Square test (α = 0.05). Statistical results demonstrated that consistent utilization was significantly associated with maternal reproductive age (p = 0.037), a high level of knowledge (p < 0.001), and strong internal motivation (p < 0.001). Mothers aged 20–35 years, those with good knowledge (83.33% consistent attendance), and those with high motivation (80.00% consistent attendance) accounted for the majority of Posyandu utilization. Conversely, no significant association was found regarding formal educational level; although the population was dominated by those with basic education (89.81%), this factor did not significantly influence the probability of utilization (p = 0.398). In conclusion, the utilization of primary healthcare services in rural areas is primarily driven by cognitive understanding and psychological motivation rather than formal educational attainment. Therefore, policy interventions should transition toward behavioral engineering approaches, in which community health workers (CHWs) are actively empowered as health educators to enhance specific literacy and sustain motivation among the target population.